Investigating relationships between thromboembolic risk and left atrial structure, function, and flow characteristics as assessed with advanced magnetic resonance techniques - Spartera, M (2021)
Atrial fibrillation (AF) is associated with alterations in left atrial (LA) blood flow characteristics which, in turn, increase the risk of LA thrombus formation and, consequently, of cardioembolic stroke. Anticoagulation is highly effective in preventing ischaemic stroke in patients with AF and stroke risk factors. More recently, it has been suggested that a cardioembolic aetiology may also underlie a proportion of ischaemic strokes that occur in sinus rhythm (SR) in the context of an atrial myopathic process caused by increased exposure to clinical risk factors, before the onset of AF. To date, it is still unclear whether LA myopathy is linked to increased embolic stroke risk and whether this association is causally determined.